Differential regulation of β-catenin-mediated transcription via N- and C-terminal co-factors governs identity of murine intestinal epithelial stem cells - Borrelli, Costanza; Valenta, Tomas; Handler, Kristina; Vélez, Karelia; Gurtner, Alessandra; Moro, Giulia; Lafzi, Atefeh; Roditi, Laura de Vargas; Hausmann, George; Arnold, Isabelle C; Moor, Andreas E; Basler, Konrad (Nature communications, 2021)
The homeostasis of the gut epithelium relies upon continuous renewal and proliferation of crypt-resident intestinal epithelial stem cells (IESCs). Wnt/β-catenin signaling is required for IESC maintenance, however, it remains unclear how this pathway selectively governs the identity and proliferative decisions of IESCs. Here, we took advantage of knock-in mice harboring transgenic β-catenin alleles with mutations that specifically impair the recruitment of N- or C-terminal transcriptional co-factors. We show that C-terminally-recruited transcriptional co-factors of β-catenin act as all-or-nothing regulators of Wnt-target gene expression. Blocking their interactions with β-catenin rapidly induces loss of IESCs and intestinal homeostasis. Conversely, N-terminally recruited co-factors fine-tune β-catenin's transcriptional output to ensure proper self-renewal and proliferative behaviour of IESCs. Impairment of N-terminal interactions triggers transient hyperproliferation of IESCs, eventually resulting in exhaustion of the self-renewing stem cell pool. IESC mis-differentiation, accompanied by unfolded protein response stress and immune infiltration, results in a process resembling aberrant "villisation" of intestinal crypts. Our data suggest that IESC-specific Wnt/β-catenin output requires selective modulation of gene expression by transcriptional co-factors.
Keywords: genetická transkripce; buněčná diferenciace; signální transdukce; Signal Transduction; hyperplazie; sekvence nukleotidů; messenger RNA; Algorithms; beta-katenin; Transcription Factors; Transcription, Genetic; Mutant Proteins; střevní sliznice; mutace; mutantní proteiny; Phenotype; chromatin; zvířata; proliferace buněk; myši; Hyperplasia; JNK mitogenem aktivované proteinkinasy; JNK Mitogen-Activated Protein Kinases; Mice; Chromatin; Stem Cells; RNA, Messenger; restrukturace chromatinu; homeostáza; Base Sequence; fenotyp; Cell Proliferation; Homeostasis; Cell Differentiation; Chromatin Assembly and Disassembly; Organoids; algoritmy; beta Catenin; organoidy; kmenové buňky; transkripční faktory; Animals; Mutation; Intestinal Mucosa